THE NEED FOR A LEGAL-WRITING COURSE IN THE SOUTH AFRICAN LLB CURRICULUM - Neels Swanepoel; Elizabeth Snyman-Van Deventer (Obiter, 2021)
Students are generally unprepared to study law. Unpreparedness includes language and writing deficiencies. Legal-writing courses at law school only lay the foundation for these skills that have to be developed and improved over many years of practice. Law schools and the organized profession should accept joint responsibility for laying this foundation. A substantial part of most legal-writing courses must include language training. Legal writing is generally not regarded as necessary by many South African law faculties. The main challenge in the area of developing legal-writing courses in South Africa involves the fact that legal academics have not been formally trained to teach language and writing. It is proposed that a course is introduced for law teachers in and that they undergo training that will enable law lecturers to present these courses themselves.